PENGEMBANGAN BAHAN AJAR MENGGUNAKAN FLIP PDF BERBASIS ETNOMATEMATIKA PADA TARI BADAYA WIRAHMASARI RANCAEKEK - Farhan Maulana Dharsono; Listiyani Permatahati Mawadah; Nani Ratnaningsih (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
This article focuses on a study that produces teaching material using an ethnomathematics-based flip PDF regarding the material and types of angles that can help the learning process in the classroom. The method used was Research and Development (R&D). The model of developmental research used was adopted from Robert Maribe Brach (2009), which consisted of five stages, the analysis, the design, the development, the implementation, and the assessment and evaluation. The subjects involved 35 students of class VII at SMPN 1 Kawali. The data analysis technique was carried outthrough quantitative descriptive analysis. Data were collected through interviews and observations. The results of the study that was obtained from an overall average score of material experts were 92.27% with a very good category. Subsequently, the overall average score of media experts was 84.53% in the very good category. In addition, the results obtained from the practicality test based on a small group was 91% with a very practical category. Thus, it was obtained teaching materials using flip PDF based on ethnomathematics of Badaya Wirahmasari Rancaekek dance on material and types of angles that were feasible and practical to use.